2006
DOI: 10.1242/dev.02473
|View full text |Cite
|
Sign up to set email alerts
|

Axis specification and morphogenesis in the mouse embryo requireNap1, a regulator of WAVE-mediated actin branching

Abstract: Dynamic cell movements and rearrangements are essential for the generation of the mammalian body plan, although relatively little is known about the genes that coordinate cell movement and cell fate. WAVE complexes are regulators of the actin cytoskeleton that couple extracellular signals to polarized cell movement. Here, we show that mouse embryos that lack Nap1, a regulatory component of the WAVE complex, arrest at midgestation and have defects in morphogenesis of all three embryonic germ layers. WAVE protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 49 publications
6
118
1
Order By: Relevance
“…Support for this idea can be found in embryos deficient in Nap1, a regulator of WAVE-mediated actin dynamics. These embryos display AVE migration defects, and, as a consequence, inhibitors of posteriorizing signals are not delivered to the right place, leading to axis duplication (Rakeman and Anderson 2006). Importantly, Nap1 −/− embryos do not show the kind of ectopic T expression or BM breakdown that we detect in FLRT3 −/− embryos.…”
Section: Discussionmentioning
confidence: 73%
“…Support for this idea can be found in embryos deficient in Nap1, a regulator of WAVE-mediated actin dynamics. These embryos display AVE migration defects, and, as a consequence, inhibitors of posteriorizing signals are not delivered to the right place, leading to axis duplication (Rakeman and Anderson 2006). Importantly, Nap1 −/− embryos do not show the kind of ectopic T expression or BM breakdown that we detect in FLRT3 −/− embryos.…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown that Nap1 is essential for a series of actin-mediated cell-migration events during early mouse embryogenesis (32). These events include migration of the anterior visceral endoderm, required for specification of the anteriorposterior body axis of the animal, and migration of the mesoderm and endoderm germ layers (32). As a WAVE complex component, Abi1 is involved in the regulation of cell migration; therefore it was expected that Abi1 also might regulate morphogenetic events during early mouse embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, inactivation of murine WAVE2 is lethal by E12.5 (during mid-gestation) (16); inactivation of N-WASP is lethal at E11.0 (during organogenesis) (33,41); inactivation of Cdc42 is lethal at E3.5 (during implantation) (42); inactivation of Nap1 is lethal at E9.0 (during gastrulation); and inactivation of Rac1 is lethal at E7.5 (during gastrulation) (32,43,44). Abi2 mutants are viable and without morphological defects (27).…”
Section: Discussionmentioning
confidence: 99%
“…WAVE2-deficient mice exhibit impaired vascular remodeling in response to growth factor stimulation (24). Further, mouse mutants of Nap1, a direct binding partner of Abi1 in the WAVE complex, also exhibit defective chorioallantoic fusion, and other developmental phenotypes associated with defects in cell migration and adhesion (34). Interestingly, heterozygous insertional mutants of Nap1, which display neural tube closure defects, also have dramatic reductions in vessel diameter (35).…”
Section: Discussionmentioning
confidence: 99%